Assent and consent in adolescent research: teachers’ perspectives from a developing country - Alomari, Mahmoud A. (Heliyon, 2020)
Teachers play a vital role in facilitating research in schools. However, teachers' views of informed consent/assent for children participation in research in the Middle East have not been investigated. In this study, focus group interviews were conducted to understand high-school teachers' perspectives toward adolescent assents and consents. The teachers indicated that parent consent is important and should be coupled with sufficient information about the research study. The teachers added that assent is most important for children above 13 years old. Conversely, the teachers believed that parent approval is only important for invasive (such as research involves blood withdrawal) but not simple procedures. Most importantly, for procedures that are considered simple, part of the teachers do not acknowledge the significance of parental approval, such as body weight, or beneficial, such as new treatment. The results indicate that some of the teachers’ views were consistent with proper conduction of pediatric research. However, other views were worrisome and might warrant further studies and actions. Risks related need to be assessed and policies needs to be developed in order to ensure the proper conduction of pediatric research.